HYBRID AI FRAMEWORK FOR EFFICIENT ANOMALY DETECTION IN VIDEO SURVEILLANCE DATA - Бондарчук, Андрій; Бушма, Олександр; Довженко, Тимур; Гашко, Андрій (SWorldJournal, 2025)
Contemporary video surveillance infrastructure produces substantial data streams, posing challenges for efficient real-time processing. Current automated anomaly detection techniques frequently demand extensive computational resources and function as opaq